Characterization of the new isotopic reference materials IRMM-524A and ERM-AE143 for Fe and Mg isotopic analysis of geological and biological samples. Issue 11 (2nd September 2020) - González de Vega, Claudia; Chernonozhkin, Stepan M.; Grigoryan, Rosa; Costas-Rodríguez, Marta; Vanhaecke, Frank
Abstract : Isotopic reference materials (IRMs) are crucial for securing accurate and precise isotope ratio measurements of non-traditional stable isotopic systems and for enabling comparison of isotope ratio data obtained at different labs. Abstract : Isotopic reference materials (IRMs) are crucial for securing accurate and precise isotope ratio measurements of non-traditional stable isotopic systems and for enabling comparison of isotope ratio data obtained at different labs. Fe and Mg isotopic analysis have gained considerable interest as it expands our understanding of critical geological and biological processes. However, the isotopic reference materials used for Fe (IRMM-014) and Mg (DSM3) isotopic analysis are either out of stock or not readily available. In this work, we report on the use of multi-collector inductively coupled plasma-mass spectrometry (MC-ICP-MS) for determination of the isotopic composition of the two new isotopic reference materials IRMM-524A and ERM-AE143, which can be used for high-precision isotopic analysis of Fe and Mg, respectively, instead of IRMM-014 and DSM3. The Fe isotopic composition of IRMM-524A, determined as the intercept of the best-fitting straight line (linear regression) through the data points for multiple reference materials of geological and biological origin, measured relative to both the conventional and new isotopic reference materials is δ 56 FeIRMM-014 = −0.004 ± 0.014‰ (2SD) and δ 57 FeIRMM-014 = +0.005 ± 0.024‰ (2SD), and thus, within the experimental uncertainty it is the same as the value for IRMM-014. Using the same regression method, ERM-AE143 is shown to be isotopically lighter than DSM3, with δ 26 MgDSM3 = −3.295 ± 0.040‰ (2SD), and δ 25 MgDSM3 = −1.666 ± 0.043‰ (2SD). These new reference materials can be recommended as secondary isotopic standards or as a replacement for the conventional or primary reference materials when these become exhausted. Additionally, we provide a comprehensive set of Fe and Mg isotopic compositions for 21 geological and 10 biological reference materials, as a contribution to the field of isotope geochemistry, as well as to the blooming field of isotope ratio applications in biomedicine.